Distinct subcortical tau burden: The tau pallido‐claustral ratio separates progressive supranuclear palsy and corticobasal degeneration. (20th October 2021) - Zhao, Chelsey ShengQi; Yan, Lei; He, Wenqing; Ang, Lee Cyn; Zhang, Qi
Abstract: Neuropathological diagnosis of progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD) requires interpretation of tau morphology based on extensive brain sampling. Here we report subcortical tau burden is sufficient to distinguish PSP and CBD, regardless of the tau morphology. The tau pallido‐claustral ratio is a promising diagnostic indicator for PSP and CBD. Abstract : A distinct tau distribution pattern is shown on the "core" brain slide. Corticobasal degeneration (CBD) has an overall high tau burden across all regions. Progressive supranuclear palsy (PSP) shows a higher tau pathology along the pallido‐nigro‐luysian axis. A higher tau pallido‐claustral ratio (>1.5) has a high possibility to be PSP.